Typification and taxonomic notes of Smilacaceae species in Java - Lulut Dwi Sulistyaningsih; Abinawanto Abinawanto; Marlina Ardiyani; Andi Salamah; Agus Haryadi (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Smilacaceae is known as a taxa with wide phenotypic variation and their taxonomical complexities remain unsolved. The three species of Smilacaceae housed in Java, are given nomenclature history. Since all the potential sources of original material have been investigated, but nothing has been identified, three neotypifications were designated here. Herbarium specimen of Koorders 34990β in Herbarium Bogoriense (BO) was chosen as the neotype of Smilax klotzschii. The de Groot & Wehlburg RD52 herbarium specimen in BO was chosen as the neotype of S. nageliana and Blume 463 herbarium specimen in L was chosen as the neotype of S. odoratissima.